Determination of Carbohydrate, Total Antioxidant, and Mineral Concentrations of Linaria triphlla (L) (Om lawlad), Malva parviflora Linn L. (Khabiza), and Myrtus communis L. (Birsim) Plants - Khadijah Al-Awjali; Mona Khanfar; Farag El-Mokasabi; Zuhir Akrim; Hamad Hasan (AlQalam Journal of Medical and Applied Sciences, 2025)
This study investigated the biochemical composition of three plant species growing in northeastern regions of Libya: Linaria triphlla (Om lawlad), Malva parviflora (Khabiza), and Myrtus communis (Birsim). Leaves and stems were analyzed to determine antioxidant capacity, total phenol content, carbohydrate levels, and mineral concentrations (sodium, potassium, calcium). Spectrophotometry was used to estimate antioxidants, phenols, and carbohydrates, while flame photometry measured mineral content. Results revealed notable variations between leaves and stems. Total phenol content fluctuated between 194.61–295.45 ppm in leaves and 283.449–313.770 ppm in stems, indicating higher phenolic concentrations in stems. Antioxidant values showed minimal variation, ranging from 9.703–9.96 ppm in leaves and 10.198–10.528 ppm in stems. Carbohydrate levels were generally low, with values between 0.016–0.134 ppm in leaves and 0.155–0.419 ppm in stems. Mineral analysis demonstrated greater differences. Sodium concentrations ranged from 0.625–1.208 ppm in leaves and 1.88–16.88 ppm in stems, showing a marked increase in stems. Potassium levels were consistently higher in stems compared to leaves, while calcium concentrations were relatively small in leaves (0.12–0.68 ppm) but higher in stems (0.375–1.541 ppm). Overall, the study highlights those stems of the selected plants generally contain higher levels of phenols, minerals, and carbohydrates compared to leaves, while antioxidant capacity remains relatively stable across plant parts. These findings provide insight into the nutritional and biochemical properties of native Libyan plants, emphasizing their potential value in food science, pharmacology, and traditional medicine.